2009
DOI: 10.1051/0004-6361/200810425
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of runaway stellar collision products

Abstract: In the cores of young dense star clusters, repeated stellar collisions involving the same object can occur. It has been suggested that this leads to the formation of an intermediate-mass black hole. To verify this scenario we compute the detailed evolution of the merger remnant of three sequences, then follow the evolution until the onset of carbon burning, and estimate the final remnant mass to determine the ultimate fate of a runaway merger sequence. We use a detailed stellar evolution code to follow the evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
204
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(208 citation statements)
references
References 57 publications
4
204
0
Order By: Relevance
“…Another model [26] studies the progressive accumulation of mass into a large (> 50 M ) seed black hole via coalescence of a population of smaller black holes. However, the existence of binaries with IMBH components remains uncertain since stellar winds may stall the growth of the IMBH progenitors in the runaway collision scenario [27], or the merger recoil may also eject a newly formed black hole from the globular cluster [28,29].…”
Section: A Intermediate Mass Black Hole Formationmentioning
confidence: 99%
“…Another model [26] studies the progressive accumulation of mass into a large (> 50 M ) seed black hole via coalescence of a population of smaller black holes. However, the existence of binaries with IMBH components remains uncertain since stellar winds may stall the growth of the IMBH progenitors in the runaway collision scenario [27], or the merger recoil may also eject a newly formed black hole from the globular cluster [28,29].…”
Section: A Intermediate Mass Black Hole Formationmentioning
confidence: 99%
“…In close binary systems, a merger (or even multiple mergers) of the C+O core from an evolved WR star with another hydrogen-deficient star, like a neutron star, a white dwarf, or WR star could occur [6,10,18]. Such processes could form a dense C+O CSM or common envelope.…”
Section: Origin Of Circumstellar Mattermentioning
confidence: 99%
“…Various authors have inferred highly nonconservative evolution for Algols, systems which are currently undergoing stable mass transfer (e.g., Refsdal et al 1974;de Greve & Linnell 1994;Figueiredo et al 1994;van Rensbergen et al 2006;† Glebbeek et al (2009) suggested that a chain of multiple stellar collisions in the dense centre of a star cluster may also enrich the interstellar medium with processed material. et al 2007).…”
Section: Binaries As Sources Of Enrichmentmentioning
confidence: 99%